Development of modified shotput devices: how are the Orthodox and Obrien styles implemented? - Heru Sulistianta; Fitri Agung Nanda; Hauzan Ariq Abdurarahman (Jurnal Keolahragaan, 2022)
The development of shotput media is one way that physical education teachers can maximize learning outcomes. The research aims to reveal the development of the results shotput modification tool and the results of the implementation effectiveness modified tool through the orthodox and Obrien styles. This research uses the development of Borg and Gall and effectiveness test research. The modified tool was assessed by material, and media experts and has been tested with the results to be presented in the sub-subexplanation explanation results and discussion. Furthermore, after the results are obtained regarding the appropriate modification tools that can be used, the effectiveness test of the two forces in the shotput is carried out. The research subjects were 30 seventh-grade students of SMP Negeri 17 Sungailangka Gedong Tataan, Pesawaran Regency. Analysis data was used in this study using the Ancova test which was carried out to see the rest difference in repulsion forces. Then perform the N-Gain Test to determine the effective application of two repulsive forces. The results revealed that the modified tool developed in both learning and effectiveness tests revealed that the developed tool had a significance of 0.00 0.05. The average orthodox force n-gain test increased by 0.44 which means that the N-Gain has increased. The results of the O'Brien style N-Gain have an average of 0.19 increase in learning outcomes using tool modifications. Based on the results, it can be concluded that there is a significant effect in the use of tool modifications on the ability to put down and place bullets using Orthodox and O'brien styles.